MALAYSIA, THAI RESEARCH UNIVERSITIES COLLABORATE TO ASSIST B40 GROUP - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 18 December 2015 – Five Malaysian and seven Thai research universities have reached an agreement to establish cooperation in looking for solutions to problems faced by the bottom 40 percent group in society or B40 in both countries.